Perfil sanguíneo de híbridos de surubim (Pseudoplatystoma reticulatum X P. coruscans) criados em diferentes densidades de estocagem - Carla Rosa Labarrere (2011)
Fish of the Pseudoplatystoma genus are known for their high growth rate and good carcass yield, as well as for their meat has a delicate flavor and no intramuscular spines. Many studies have been conducted aiming to determine the best growing conditions for them. In these situations, the blood profile may be an important tool, since it is considered as an indicator of fish health, helping to determine the influence of management on the homeostasis of these animals, allowing early detection of conditions that are affecting production performance. Given this context and the lack of information about the haematological, biochemical and protein profile of Pseudoplatystoma spp., this study aimed to analyze the blood profile of hybrid surubim (P. reticulatum X P. coruscans) submitted to different stocking densities in recirculating water system in two distinct stages of production, from 150 to 400 g (Experiment 1) and 400 to 1000 g (Experiment 2). The concentration of haemoglobin (Hb), packed volume cell (PVC), mean corpuscular haemoglobin concentration (MCHC), total and fractionated proteins, glucose, cholesterol, triglycerides, urea, creatinine, alkaline phosphatase (ALP), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), calcium, phosphorus, potassium and magnesium were obtained. Possible, the values of total protein, albumin, beta and gamma globulins, glucose, cholesterol, urea, ALP, AST, LDH, calcium and phosphorus were influenced by weight of animals. Only MCHC and urea concentrations in Experiment 1, and pre-albumin, alpha-globulin, ALP and AST in Experiment 2 were influenced by stocking density, presenting a significant difference between groups. Thus, we conclude that the hybrid fish studied, in both experiments, maintained blood homeostasis after different conditions